Pozwolenie zintegrowane jako nowe źródło wiedzy o emitentach wykorzystywanych w procesach zarządzania zasobami środowiska - Kobyłko, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article emphasizes the need for aid of environment supplies management processes on different levels. Decisions about ways of using these supplies are taken in a situation of lack of information and knowledge. The information created at various levels of environmental management does not meet the needs of the factors of these processes. The article is an attempt to example these mechanisms on the example of integrated permission. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 86-93